VALIDASI MODEL BISNIS USAHA MIKRO PADA INDUSTRI PERJALANAN WISATA (STUDI KASUS: ARJUNA TRAVEL CORNER DI KABUPATEN GARUT - Astri Gina; Mia Hendra Pratiwi (LPPM Institut Pendidikan Nusantara Global, 2023)
Indonesia's economic situation after the Covid pandemic is experiencing recovery with a slow increase in sales of small business products. One type of travel business that almost went bankrupt due to the absence of income during the pandemic has also started to carry out its business activities. This increase in activity is in line with government policies that have allowed normal business activities. However, in this post-pandemic situation, many things must be adjusted by business actors in the field of travel because people's travel needs may experience significant changes. This research aims to test innovations that will be carried out in the travel business model. This trial is essential to improve business continuity in the post-pandemic period. This research strategy uses a case study in Arjuna Travel Corner. The qualitative research approach uses data collection techniques with interviews and observations. The results showed that the new business model implemented by Arjuna Travel Corner has been valid, following the wants and needs of consumers. This research can be used as a reference for further research related to this field. Practitioners of this research are expected to be input for decision-making in carrying out business model innovations on related objects.